RESPONS 12 AKSESI KECIPIR (Psophocarpus tetragonolobus L. DC) TERHADAP PEMANGKASAN REPRODUKTIF PADA MUSIM HUJAN DI JATINANGOR - Nusifera, Sosiawan; K., Murdaningsih H.; Rachmadi, Meddy; Karuniawan, Agung (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2011)
Research aimed to know the responses of 12 winged bean accessions to reproductive pruning in rainy season, was conducted in experimental station ofagricultural faculty, Padjadjaran University started from November 2008 until May 2009. Experiment was arranged in randomized block design with split-plot pattern and replicated twice. Main plot was reproductive pruning consisted of two levels namely with (p) and without pruning (np). Whereas, sub plot was 12 winged bean accessions. Variables observed were tuber length (cm), tuber diameter (cm), tuber volume (ml), tuber weight per plant (g), number of tuber per plant, and tuber weight per plot (kg). Data were analysed using analysis of variance, if there was significant source of variance, analysis was continued with Scott Knott Cluster Analysis for genotype simple effect and LSD for pruning simple effect, with 5% level respectively. Results showed that there were different responses of each accession to reproductive pruning, especially on characters of tuber diameter, number of tuber per plant, and tuber weight per plant. Eventhough singly, pruning didn’t show significant effect on all characters observed, for tuber diameter, number of tuber per plant, andtuber weight per plot, effectiveness of pruning was seen on several accessions. Single effect of accessions was seen on tuber volume and tuber weight per plant. For tuber length, pruning, accessions and interaction of both, seemed to have no effect on it. Accessions of 8.20, 8.16, 8.29, 8.10, and 8.6 were potential genotypes for tuber production for they had tuber diameter over 2 cm.